IMPROVEMENT OF SCIENCE AND TECHNOLOGY THROUGH INTERNET OF THINGS (IOT) FOR SMART HOME APPLICATION TRAINING FOR STUDENTS OF SMK NURUL JADID PROBOLINGGO - Amalia Herlina; Ahmad Daviatu Firdausi; Sulhan Maulana Akmal Habibi; Virgan Dirgantara (Universitas Airlangga, 2021)
AbstractThe advancement of science and technology in the era of the Industrial Revolution 4.0 is developing rapidly, including the development of the Internet of Things (IoT) which makes the world smarter. An example of its implementation is the smart home system which offers advantages, so that it is currently being widely socialized in Indonesian society. This training aims to provide solutions to partner problems, namely SMK Nurul Jadid, especially Grade 12 students. There are two main problems with partners that have a high level of urgency to be resolved, namely improving science and technology, and developing 21st century competence for students. The series of activities carried out included 1) Making IoT learning media for smart home systems, 2) Learning about IoT and smart home systems, 3) Training on making smart home designs, 4) Training on assembling smart home system tools, 5) Training on the use of the Blynk Application for smart home control system 6) Development of 21st century competence (digital era literacy, effective communication, inventive thinking, and high productivity). Activity achievement is measured using the before after test (pre-test and post-test) method. From the increasing number of correct answers in the post-test, it is known that there is an increase in students' understanding of science and technology about IoT for smart home systems. Meanwhile, the achievement of 21st century competency development is measured by the value of case studies given to students in which the entire group of students achieves the predicate of GOOD. The implementation of all training activities went well. The results of the evaluation questionnaire stated that students felt that this training was very beneficial for improving science and technology and also very beneficial for the development of their competencies. Thus, this series of activities is a solution because it can solve internal problems as well as solutions to external problems of partners.Keywords: BLYNK IoT Platforms, Internet of Thing, Smart Home System, Vocational High School AbstrakKemajuan IPTEK di era Revolusi Industri 4.0 berkembang pesat dan cepat, termasuk perkembangan Internet of Things (IoT) yang membuat dunia lebih pintar. Contoh implementasinya adalah sistem smart home yang menawarkan keunggulan, sehingga saat ini mulai banyak disosialisasikan di masyarakat Indonesia. Pelatihan ini bertujuan untuk memberikan solusi permasalahan mitra yaitu SMK Nurul Jadid khususnya siswa Kelas 12. Terdapat dua permasalahan utama mitra yang memiliki tingkat urgensi tinggi untuk diselesaikan, yaitu peningkatan IPTEK dan pengembangan kompetensi abad 21 bagi siswa. Rangkaian kegiatan yang dilakukan meliputi 1) Pembuatan media pembelajaran IoT untuk sistem smart home, 2) Pembelajaran tentang IoT dan sistem smart home, 3) Pelatihan pembuatan desain smart home, 4) Pelatihan perakitan alat sistem smart home 5) Pelatihan penggunaan Aplikasi Blynk untuk sistem kontrol smart home 6) Pengembangan kompetensi abad 21 (literasi era digital, komunikasi efektif, berpikir inventif dan produktivitas tinggi). Capaian kegiatan diukur menggunakan metode tes before after (pre-test dan post-test). Dari jumlah jawaban benar yang meningkat pada post-test, diketahui adanya peningkatan pemahaman siswa terhadap IPTEK tentang IoT untuk sistem smart home. Sedangkan pencapaian pengembangan kompetensi abad 21 diukur dari nilai studi kasus yang diberikan pada siswa yang mana seluruh kelompok siswa mencapai predikat BAIK. Pelaksanaan seluruh kegiatan pelatihan berlangsung dengan baik. Hasil kuesioner evaluasi menyebutkan, siswa merasakan bahwa pelatihan ini sangat bermanfaat bagi peningkatan IPTEK dan juga sangat bermanfaat bagi pengembangan kompetensi mereka. Dengan demikian, rangkaian kegiatan ini merupakan solusi karena dapat menyelesaikan permasalahan internal sekaligus solusi permasalahan eksternal mitra.Kata kunci: Aplikasi BLYNK, Internet of Thing, Sekolah Menengah Kejuruan, Smart Home System